Effects of EMDR vs. waiting list for adults with post-traumatic stress disorder: A systematic review and meta-analysis of randomized controlled trials - Villegas-Ortega, Jose; Galvez-Arevalo, Ricardo; Castilla-Encinas, Adriam M.; Gutiérrez-González, Benjamín; Apolitano-Cárdenas, Claudia I.; Alvarez-Arias, Priscilla; Paredes-Angeles, Rubí; Taype-Rondan, Alvaro (Journal of affective disorders, 2026)
Posttraumatic Stress Disorder (PTSD) is a prevalent mental health condition that can significantly impair quality of life. Eye Movement Desensitization and Reprocessing (EMDR) has been proposed as a psychotherapeutic intervention for PTSD, yet its effects remain debated. We conducted a systematic review and meta-analysis following PRISMA 2020 guidelines to evaluate EMDR versus waiting list in adults with PTSD. Included RCTs were assessed using the Cochrane Risk of Bias Tool. Random-effects meta-analyses were performed, and evidence certainty was graded using GRADE. Twelve RCTs (n = 690 randomized participants) met the inclusion criteria. EMDR may increase the likelihood of losing PTSD diagnosis at post-treatment (Risk Ratio [RR]: 2.13; 95 % CI: 1.08–4.23) and follow-up (RR: 3.56; 95 % CI: 0.82–15.48), although the evidence is very uncertain. EMDR may also reduce PTSD symptoms at post-treatment (standardized mean difference [SMD]: -1.19; 95 % CI: −1.70 to −0.68) and follow-up (SMD: -0.88; 95 % CI: −1.62 to −0.13), although evidence certainty remains low to very low. Similar trends were observed for depression, anxiety, social disability, and sleep disturbances, but long-term effects remain unclear. No study assessed relevant outcomes such as quality of life, treatment acceptability, or adverse effects. Risk of bias, particularly due to lack of shielding and allocation concealment, further limits confidence in these findings. Although EMDR may reduce PTSD symptoms and increase the likelihood of diagnostic remission compared to a waiting list, the certainty of the evidence is low to very low, and its long-term effects remain unknown. •EMDR may reduce PTSD symptoms compared to waiting list at post-treatment.•Evidence suggests EMDR may increase diagnostic remission in PTSD patients.•Effects of EMDR on depression, anxiety, and sleep showed similar patterns.•Certainty of evidence was low to very low due to methodological limitations.•Long-term effects, quality of life, and safety of EMDR remain unclear.